2006
DOI: 10.1111/j.1462-2920.2006.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemostat‐based proteomic analysis of toluene‐affected Pseudomonas putida S12

Abstract: The aim of this study was to assess the cellular response of the solvent-tolerant Pseudomonas putida S12 to toluene as the single effector. Proteomic analysis (two-dimensional difference-in-gel-electrophoresis) was used to assess the response of P. putida S12 cultured in chemostats. This approach ensures constant growth conditions, both in the presence and absence of toluene. A considerable negative effect of toluene on the cell yield was found. The need for energy in the defence against toluene was reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 36 publications
10
87
0
Order By: Relevance
“…This confirmed that the effect of different nutrient limitations on global gene expression is larger than the effect of the presence of toluene. The residual concentration of glucose and nitrogen in the steady state cultures of P. putida S12 was similar to the previous study (Volkers et al 2006), the decrease in the biomass yield in the presence of toluene (data not shown) was comparable to earlier findings (Isken . 1999).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This confirmed that the effect of different nutrient limitations on global gene expression is larger than the effect of the presence of toluene. The residual concentration of glucose and nitrogen in the steady state cultures of P. putida S12 was similar to the previous study (Volkers et al 2006), the decrease in the biomass yield in the presence of toluene (data not shown) was comparable to earlier findings (Isken . 1999).…”
Section: Resultssupporting
confidence: 81%
“…Our finding that the hypothetical protein PP3611 was down-regulated (Volkers et al 2006) was confirmed at the transcriptional level. We furthermore established the relationship between PP3611, renamed TrgI, and toluene tolerance and present evidence that the down-regulation of TrgI is part of the first line of defence against toluene in P. putida S12.…”
Section: Electronic Supplementary Materialssupporting
confidence: 69%
See 2 more Smart Citations
“…Similarly, solvent-tolerant P. putida S12 up-regulated the OprH porin (12-fold) upon toluene stress, probably to stabilize the outer membrane (48). Furthermore, the occurrence of OmpC as several 2D electrophoresis-separated spots with different pI values, as well as molecular weights (Fig.…”
Section: Resultsmentioning
confidence: 99%